Evidence of oral health intervention during pregnancy for spontaneous preterm birth reduction: An integrative review - Cristina Dutra Vieira; Andreza Nayla de Assis Aguiar; Camilla Aparecida Silva de Oliveira Lima; Zilma Silveira Nogueira Reis (Wolters Kluwer Medknow Publications, 2022)
Oral health care is critical for overall well-being, which is associated with better obstetric outcomes. The aim of the present integrative review was to assess scientific reports to support the planning of effective oral health interventions to prevent preterm birth (PTB) and low birth weight (LBW), as a secondary target. Seven bibliographic bases were searched from 2013 to 2018. Studies including oral health interventions during antenatal care with measurable impact on PTB or LBW reduction were searched. Sixteen studies were included. The heterogeneity in the population of pregnant women, and the types of oral intervention as well as the lack of accurate gestational ages, made it difficult to summarize the evidence. Despite the early intervention in high-risk groups, there was not enough evidence to support a significant reduction in PTB rates. There was some evidence that untreated periodontal disease in pregnancy was associated with LBW. This review did not provide strong evidence that preventive oral interventions during pregnancy had a measurable impact on spontaneous PTB reduction. However, further research is needed to clarify the impact of oral health interventions on the general pregnant women population or on those with a high risk of PTB and LBW.